Polymeric hybrid and composite materials containing functionalized polyhedral oligomeric silsesquioxanes (POSS) - Andrzejewska, E.; Marcinkowska, A.; Prządka, D.; Kloziński, A.; Jakubowska, P. (Polimery, 2013)
The paper presents a review of investigations carried out in Polymer Department at Poznan University of Technology within the project „Silsesquioxanes as nanofillers and modifiers in polymer composites”. Research focused on the modification of poly(meth)acrylates obtained by photopolymerization, polyurethanes synthesized in bulk or in a solvent (both in situ modifications) and polyolefins (modification during processing) by functionalized polyhedral oligomeric silsesquioxanes (POSS). The effects of the addition of POSS on photopolymerization kinetics of methacrylates (Figs. 1, 2, 6, 7), physical and mechanical properties of the resulting hybrid and composite poly(meth)acrylate materials (Figs. 3—5, 8), as well as mechanical properties of polyurethanes (Fig. 9) and rheological properties of polyolefins (Fig. 10—12) are discussed.